PERSPEKTIF HISORIS ARKEOLOGIS TENTANG KERAGAMAN BENTUK BENTUK MASJID TUA DI NUSANTARA - A Gafur (Sosial Budaya, 2015)
In the early history of Islam, the mosque which literally means place of prostration did not refer to a building with a roof or boundary. Most important is the place of prostration. But in subsequent developments, the mosque became more specific sense, namely a building even the environment walled and used as a place of prayers. Mosque as a building is a realization and physical aspects of Islamic culture. The Prophet never provide normative guidelines on how the shape of the mosque building. Therefore, it is natural, there are various forms of structure and ornament mosque were found in various parts of the Islamic world, including in the Nusantara. The shape and structure of the ornament is dependent on the culture that existed before. It is also easily found all over the archipelago, the shape and ornamentation are influenced by elements of the pre-Islamic, but also influenced by foreign cultures such as China, the Middle East and Europe.